2020
DOI: 10.1029/2019jg005429
|View full text |Cite
|
Sign up to set email alerts
|

Top‐Down Constraints on Methane Point Source Emissions From Animal Agriculture and Waste Based on New Airborne Measurements in the U.S. Upper Midwest

Abstract: Agriculture and waste are thought to account for half or more of the U.S. anthropogenic methane source. However, current bottom-up inventories contain inherent uncertainties from extrapolating limited in situ measurements to larger scales. Here, we employ new airborne methane measurements over the U.S. Corn Belt and Upper Midwest, among the most intensive agricultural regions in the world, to quantify emissions from an array of key agriculture and waste point sources. Nine of the largest concentrated animal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…For anthropogenic emissions, we employ a scale-dependent uncertainty (encompassing magnitude and displacement uncertainties) following Maasakkers et al (2016); the resulting error standard deviation averages 40 %-105 % across sectors over our study region. For other sources we assume a prior error standard deviation of 50 % following earlier studies (Maasakkers et al, 2019;Turner et al, 2015;Wecht et al, 2014;Zhang et al, 2018;Sheng et al, 2018b). For inversions optimizing the total methane flux across sectors, the above terms are combined in quadrature as the diagonal elements of the prior error covariance matrix.…”
Section: Cost Function and Error Specificationmentioning
confidence: 99%
“…For anthropogenic emissions, we employ a scale-dependent uncertainty (encompassing magnitude and displacement uncertainties) following Maasakkers et al (2016); the resulting error standard deviation averages 40 %-105 % across sectors over our study region. For other sources we assume a prior error standard deviation of 50 % following earlier studies (Maasakkers et al, 2019;Turner et al, 2015;Wecht et al, 2014;Zhang et al, 2018;Sheng et al, 2018b). For inversions optimizing the total methane flux across sectors, the above terms are combined in quadrature as the diagonal elements of the prior error covariance matrix.…”
Section: Cost Function and Error Specificationmentioning
confidence: 99%
“…This agrees with our findings here of a +15% adjustment for beef facilities (dominated by enteric emissions) and an approximate +30% summer and winter adjustment for dairies and hog facilities (with a larger role for manure emissions). In our previous work, we applied aircraft-based mass balance to quantify facilitylevel emissions for concentrated animal feeding operations in the Upper Midwest and found (as here) good topdown/bottom-up agreement for enteric emissions but discrepancies for manure (Yu et al, 2020). A recent site-level study at a large Wisconsin dairy farm observed low manure emissions (~30% of the enteric flux) owing to frequent field application throughout the year (Wiesner et al, 2020), further supporting our characterization of manure management as a key uncertainty in current large-scale bottom-up inventories.…”
Section: Livestock Methane: Enteric Emissions Well-represented But Lamentioning
confidence: 64%
“…Along with mixed-layer surveying, each flight included 1-2 vertical profiles to characterize the atmosphere's vertical structure from the surface to lower free troposphere. The GEM flights also included extensive point source characterization as described by Yu et al (2020).…”
Section: Gem Flights and Measurement Payloadmentioning
confidence: 99%
See 2 more Smart Citations